Six Sigma Software Development, Second Edition - Tayntor, Christine (CRC Press, 2009)
Even though Six Sigma programs have successfully been implemented in practice, many IT departments remain skeptical of the process or are unaware of how the tools can be used to improve system development. Removing the mystique surrounding this technique, Six Sigma Software Development, Second Edition demonstrates how Six Sigma tools and concepts can be used to enhance the system development process.